SAT0182 Tocilizumab s.c. – improvement of the depressiveness, fatigue and pain in ra therapy. (12th June 2018) - Behrens, F.; Englbrecht, M.; Biewer, W. A.; Burmester, G.-R.; Feuchtenberger, M.; Flacke, J.-P.; Hofmann, M.; Kästner, P.; Kellner, H.; Klopsch, T.; Kühne, C.; Tony, H.-P.; et al.
Abstract : Background: The non-interventional ARATA study (NCT02251860 ) observes the clinical effectiveness and safety of subcutaneous Tocilizumab [TCZ] s.c. treatment under routine conditions over a 2-year period. Objectives: In this interim analysis, the treatment with TCZ s.c., in particular with respect to patient-reported outcomes regarding depression, fatigue and pain, was evaluated. Methods: TCZ-naive patients (Pts) (≥18 years) with RA, who receive TCZ s.c. treatment, could be included in the study since 2014. Demographic and disease-specific characteristics, the progression of the disease under treatment, concomitant medications, adverse events (AE) and patient questionnaires were documented. Results: This interim analysis (reporting date 01-FEB-2017) included 912 Pts. 75% of the Pts were female, the average age at baseline (BL) was 57 years, the median disease duration was 8 years. 319 Pts (35%) were pretreated exclusively with sDMARD and 585 Pts (64%) were also pretreated with bDMARD. For the readjustment, TCZ s.c. was applied for 69% without sDMARD, 31% in combination with MTX and for 66% with glucocorticoids. In the course of the study, 65% of the Pts achieved a DAS28-BSG remission. Furthermore, the functional restrictions in day-to-day life (HAQ-DI D from BL: -0.3) improved. No new safety signals were observed. By means of the Beck Depression Inventory (BDI-II) score (Englbrecht et al., Arthritis Care Res 2017; 69:58–66), validated for RA, the depressive symptoms could be documented. At baseline, 186 Pts (50%) showed no, 70 (19%) minor, 67 (18%) moderate and 47 (13%) severe depression. Under the treatment with TCZ, the depressive symptoms improved (compare figure 1). The patients reported a significant improvement of the pain (VAS: average change from BL to week 52 by -21 points and to week 104 by -24 points) as well as the fatigue (VAS: average change from BL to week 52 by -11 points and 104 by -12 points). Conclusions: In the ARATA study, TCZ s.c. demonstrated an effective and persistent reduction in the disease activity of the treated RA patients. The patients confirmed improved physical functionality as well as less fatigue and pain. Depression plays an important role in RA, as the results of BDI-II highlight, whereby the depressive symptoms also improved distinctively under treatment with TCZ s.c. Disclosure of Interest: F. Behrens Grant/research support from: Abbvie, Pfizer, Roche, Chugai, Janssen, Novartis, Consultant for: Abbvie, Pfizer, Roche, Chugai, UCB, BMS, Celgene, MSD, Novartis, Biotest, Janssen, Genzyme, Lilly, Boehringer, Sandoz, M. Englbrecht: None declared, W. A. Biewer: None declared, G.-R. Burmester Consultant for: Lilly, Pfizer, Sanofi, Roche, M. Feuchtenberger Consultant for: MSD, Roche, Abbvie, Chugai, Pfizer, UCB, J.-P. Flacke Employee of: Roche Pharma AG, M. Hofmann Employee of: Chugai Pharma Europe Ltd., P. Kästner: None declared, H. Kellner Consultant for: Roche, T. Klopsch: None declared, C. Kühne Consultant for: Celgene, Roche, Pfizer, Novartis, BMS, H.-P. Tony Consultant for: Roche Pharma, Abbvie, BMS, Chugai, Janssen, Novartis, Sanofi, Lilly, Speakers bureau: Roche Pharma, Abbvie, BMS, Chugai, Janssen, Novartis, Sanofi, Lilly, C. Amberger Consultant for: Chugai, AbbVie, Celgene, MSD, Pfizer, BMS, HexaL